Designing a Comprehensive Evaluation Model for Health System Reform Plan in Iran: An Approach to Extended Balanced Scorecard - Janbazi, Shahriar; Rabiee Mandejin, Mohammad Reza; Eslambulchi, Alireza; Bahadori monfared, Ayad (Novelty in Biomedicine, 2019)
Background: Health and striving to maintain and promote it has always been an important priority in governments, communities, and public policies. To implement health objectives through the Fifth Five-Year National Development Plan of Iran, the health system reform plan with three approaches to the financial protection of the public, creating equity in access to health services, and improving the quality of services has been on the government’s agenda since 05.05.2014. Investigations revealed that the lack of a comprehensive and scientific model for evaluating this national program is evident. This study aimed to design a comprehensive model of health reform plan evaluation in Iran. What distinguishes this study from previous studies is the simultaneous attention to the challenges of performance evaluation, social responsibility, and examining them in a comprehensive and coherent model. Materials and Methods: The present study considered as descriptive-survey research in terms of strategy. The research method was a combination that conducted from 2018 to 2019. The sample size of the qualitative part of the research consisted of 17 academic and executive health experts selected by purposive non-random sampling. In the quantitative part of the study, 400 health service providers selected by stratified random sampling. In this study, content analysis and Delphi technique, and Expert choice v24, SPSS V22 and AMOSV14 software were used to collect, classify, deduce and exploit data, and questionnaires. Results: The findings of this study resulted in the design of a 900-scorecard model of the comprehensive evaluation of the health system reform plan in Iran based on 5 dimensions (finance, social responsibility, growth and learning, clients and internal processes), 17 components and 70 indicators. Conclusion: The findings of the quantitative section of the study showed that the indicators, dimensions and levels of the comprehensive evaluation model for health system reform plan in Iran (CEHSRP-IR) qualified for evaluation of the effectiveness of this national program at different organizational levels and executing units of health system reform plan in Iran.